Human disturbance in riparian areas disrupts predator–prey interactions between grizzly bears and salmon - Megan S. Adams; Taal Levi; Mathieu Bourbonnais; Christina N. Service; Kyle Artelle; Heather Bryan; Paul Paquet; Trisalyn Nelson; Chris T. Darimont (Ecology and Evolution, 2024)
Abstract Wildlife must increasingly balance trade‐offs between the need to access important foods and the mortality risks associated with human‐dominated landscapes. Human disturbance can profoundly influence wildlife behavior, but managers know little about the relationship between disturbance–behavior dynamics and associated consequences for foraging. We address this gap by empirically investigating the consequences of human activity on a keystone predator–prey interaction in a region with limited but varied industrial disturbance. Using stable isotope data from 226 hair samples of grizzly bears (Ursus arctos horribilis) collected from 1995 to 2014 across 22 salmon‐bearing watersheds (88,000 km2) in British Columbia, Canada, we examined how human activity influenced their consumption of spawning salmon (Oncorhynchus spp.), a fitness‐related food. Accounting for the abundance of salmon and other foods, salmon consumption strongly decreased (up to 59% for females) with increasing human disturbance (as measured by the human footprint index) in riparian zones of salmon‐bearing rivers. Declines in salmon consumption occurred with disturbance even in watersheds with low footprints. In a region currently among the least influenced by industrial activity, intensification of disturbance in river valleys is predicted to increasingly decouple bears from salmon, possibly driving associated reductions in population productivity and provisioning of salmon nutrients to terrestrial ecosystems. Accordingly, we draw on our results to make landscape‐scale and access‐related management recommendations beyond current streamside protection buffers. This work illustrates the interaction between habitat modification and food security for wildlife, highlighting the potential for unacknowledged interactions and cumulative effects in increasingly modified landscapes.